An Efficient and Cost-effective Modified Carbon Paste Electrodes for Diltiazem Hydrochloride Determination in Tablets - Sanafery, Safa S. EL; Elshafei, Mostafa F.; Khalf‐Alla, Perihan A.; Mohamed, Gehad G. (Current Analytical Chemistry, 2025)
Background and ObjectiveThis study presented new sensitive and selective modified carbon paste (MCPE) potentiometric sensors modified with different ion pairs for the determination of the antihypertensive drug diltiazem hydrochloride (DTM-HCl) in biological fluids, pharmaceutical preparations, and in its pure form.MethodsPlasticizers, ion pair type, ion pair content, response time, temperature, and pH were just a few of the experimental factors evaluated that were found to affect electrode efficiency. The two electrodes that show the best sensitivity were prepared by mixing diltiazem-tetraphenyl borate (DTM-TPB) ion pair, graphite, and TCP or o-NPOE as a plasticizer.ResultsOver the concentration ranges of 1.0x10-5–1.0x10-2, the produced electrodes I and II demonstrated monovalent Nernstian responses of 55.7±0.902 and 57.6±0.451 mV decade-1. The selectivity property of the suggested electrodes was used to study the interference ions. The concentration of DTM-HCl in pharmaceutical formulations and biological fluids was measured using these modified electrodes. During the validation procedure, metrics like linearity, accuracy, precision, limit of detection, limit of quantification, and specificity were used.ConclusionThe obtained results showed good agreement with the HPLC technique as indicated by the F and t-test values and can conclude the possibility of using this potentiometric method in the routine analysis of DTM-HCl.
Keywords: HPLC